Legacy of Holocene Landscape Changes on Soil Biogeochemistry: A Perspective From Paleo‐Active Layers in Northwestern Canada. Issue 9 (3rd September 2019) - Lacelle, Denis; Fontaine, Marielle; Pellerin, André; Kokelj, Steve V.; Clark, Ian D.
Abstract: Recent climate warming is contributing to permafrost degradation and vegetation change; however, little is known about the legacy of Holocene landscape change on contemporary soil biogeochemical conditions. In permafrost soils of northwestern Canada, widespread permafrost degradation occurred during the early Holocene warm interval and its impacts on soil biogeochemistry are archived in the paleo‐active layer. Here we show contrasting profiles of soil soluble chemistry and organic carbon composition at sites affected by different types of permafrost degradation. At sites that experienced increased depth of thaw, the relict active layer contained a lower abundance of soluble ions than the underlying undisturbed permafrost; however, both the relict active layer and undisturbed permafrost contained mainly old recalcitrant organics suggesting that minor microbial degradation of organics had occurred. At sites that experienced past thaw slumping, the relict active layer had a higher solute content and contained both young‐degradable and old‐recalcitrant organics due to the integration of slumped surface organic mats into the colluvial soils or vegetation re‐colonizing the surface of the former slump. Our results show that permafrost degradation that occurred during the early to mid‐Holocene have preconditioned the biogeochemical conditions in near‐surface permafrost soils such that significant local variability exist following past landscape changes. Thus, determining the state of soil soluble chemistry and SOC in permafrost should be done within a paleo‐landscape change framework to better forecast CO2 –CH4 emissions and solutes release from thawing permafrost. Key Points: Effects of Holocene landscape changes on soil biogeochemistry are archived in relict active layer Different types of permafrost degradation have varying effects on soil biogeochemical conditions Holocene landscape changes preconditioned biogeochemical conditions in permafrost soils and the potential consequences of future thaw